A critical review of Chinese vaccine enterprises in the global aid market: evolution, drivers, and structural constraints - Ding, Mengli (Frontiers in Public Health, 2025)
The Chinese government has assumed an increasingly prominent role in global health governance in recent years, yet the engagement of Chinese enterprises remains underexplored. Existing studies have largely focused on Beijing’s major initiatives during the COVID-19 pandemic, overlooking the evolving role of Chinese enterprises as non-state actors. This article provides a comprehensive review of the participation of Chinese vaccine companies in the global aid market, with particular attention to their changing roles, underlying motivations, and persistent challenges as latecomers from the Global South. Drawing on around 80 industry and policy documents, publicly available datasets, and 10 semi-structured interviews with industry and government stakeholders, this study uses documentary synthesis and thematic analysis to show that COVID-19 marked a critical turning point, accelerating Chinese vaccine manufacturers’ international engagement while exposing persistent structural barriers. Unlike earlier studies, this review shows that Chinese vaccine enterprises’ engagement in the global aid market is shaped not only by strategic market ambitions and alignment with national public health priorities, but also by enduring structural constraints such as geopolitical tensions, institutional mistrust, talent shortages, and reputational vulnerabilities. By situating Chinese enterprises within broader debates on non-state actors in global health, the study advances existing literature and offers policy-relevant insights to strengthen their capacity and influence in promoting equitable vaccine access.